2014
DOI: 10.1371/journal.pone.0106694
|View full text |Cite
|
Sign up to set email alerts
|

Prominin-1 (CD133) Defines Both Stem and Non-Stem Cell Populations in CNS Development and Gliomas

Abstract: Prominin-1 (CD133) is a commonly used cancer stem cell marker in central nervous system (CNS) tumors including glioblastoma (GBM). Expression of Prom1 in cancer is thought to parallel expression and function in normal stem cells. Using RNA in situ hybridization and antibody tools capable of detecting multiple isoforms of Prom1, we find evidence for two distinct Prom1 cell populations in mouse brain. Prom1 RNA is first expressed in stem/progenitor cells of the ventricular zone in embryonic brain. Conversely, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…It has previously been reported that CD133 mRNA expression is negatively associated with IDH1 mutation and the G-CIMP group of Proneural GBMs [40]. Our analyses confirm this observation (p- value 0.006, t-test) (Figure S5C).…”
Section: Resultssupporting
confidence: 89%
“…It has previously been reported that CD133 mRNA expression is negatively associated with IDH1 mutation and the G-CIMP group of Proneural GBMs [40]. Our analyses confirm this observation (p- value 0.006, t-test) (Figure S5C).…”
Section: Resultssupporting
confidence: 89%
“…To do so, we utilized primary patient-derived glioblastoma tumor-initiating cells that are propagated as neurospheres in neural stem cell media to maintain their ‘stem cell-like’ properties. These cells are highly tumorigenic in vivo , and form aggressive glioblastomas upon intracranial injection into recipient mice 38 . We treated cultures of glioblastoma tumor-initiating cell lines derived from four independent patients with CVT-313, and monitored Sox2 levels.…”
Section: Resultsmentioning
confidence: 99%
“…The cell surface antigen CD133 is notoriously expressed in physiological neural stem cells, and has also been considered a suitable marker to identify GBM CSC fractions [2,109,110].…”
Section: Nps Conjugated To Cd133 Antibodymentioning
confidence: 99%